Psikoanalisis dalam Novel Sunyi Paling Riuh Karya Fajar Sulaiman - Samsiah, Siti; Rahayu, Sri (UIR Press, 2023)
This research is motivated by the personality elements of the characters in the novel Sunyi Palinng Riuh by Fajar Sulaiman Sigmund Freud's Psychoanalytic Study. In this study, the characterizations reflect the dialogues and monologues contained in the novel. The purpose of this study is to describe, analyze, interpret and conclude the personality elements of the characters in the novel Sunyi Palinng Riuh by Fajar Sulaiman in the study of Sigmund Freud's psychoanalysis. This research uses descriptive research methods and uses a qualitative approach. The data collection technique used is Hermeneutic, namely reading, noting, and concluding techniques. The data analysis technique used is data identification, data clarification, data analysis, data interpretation, and conclusions. The results of this study can be concluded that the most dominant element of the novel Silent Most Riuh by Fajar Sulaiman is ego as much as 80 data. Basically, the ego differentiates between objects that are thought of and objects in the real world. Meanwhile, the id is the principle of serenity and seeks satisfaction of desires.